Cultural Sustainability Analysis of 12 Coastal Tourism Destinations in North Jakarta - Kartika, Dewi Gita; Ismayanti; Djamhur, Ina Gandawati (Talenta Publisher, 2024)
Maintaining culture so that it remains sustainable is everyone's responsibility, because the identity of a nation can be seen from the culture. This descriptive research aims to analyze the cultural sustainability of 12 coastal tourism destinations in North Jakarta, by assessing the protection of cultural heritage and visits to cultural sites. With a quantitative approach and employing scoring analysis techniques, data were collected through observations and Focus Group Discussions (FGDs) with key informants from the 12 coastal tourism destinations in North Jakarta. The results of this study identified Tanjung Priok, Suaka Marga Satwa, Sunda Kelapa and Ancol Area are sustainable because both destinations have implemented protection of cultural assets and intangible heritage well, otherwise Bahtera Jaya Yacht Club is unsustainable because of poor management and changes in the structure of cultural heritage buildings. It is hoped that this research will be useful for further researchers and stakeholders in making policies related to cultural sustainability in Indonesia, especially North Jakarta.